LATRINE USE AND ASSOCIATED FACTORS AMONG RURAL COMMUNITY IN INDONESIA - Vera Yulyani; Dina Dwi N; Dina Kurnia (Malaysian Journal of Public Health Medicine, 2019)
Indonesia is the second-most-populated country still practicing open defecation. The low utilization of latrines is a big problem that can affect human health and the environment. Several sub-districts in Tanggamus Regency have the lowest reported use of a latrine. This study aimed to determine associated factors of latrine usage in Tanggamus Regency in 2017.. A cross-sectional study was conducted among 399 households in Tanggamus Regency, Lampung. Sampling was proportional to the total number of household in 20 sub-districts. Respondents were interviewed by a structured questionnaire . Data were analyzed using SPSS version 18.0. The study observed that a majority (55.6%) of the respondents used a latrine; furthermore, more than half of all respondents indicated good knowledge (55.9%), positive attitude (57.4%), good economic status (56.1%), access to a proper latrine (57.6%), good support from health office (55.4%), and availability of clean water (53.4%). Multivariate analysis showed that attitude was the most dominant factor related to the utilization of latrine (P<0.05 and adj OR=3.2). Encouraging communities to translate their positive attitudes into the behavior was very important. Policies, community leaders, and heads of households should all be influenced to change community attitudes to drive consistent latrine use.